THE DISTINCTIVE FEATURES OF THE CATEGORY OF GENDER IN RUSSIAN IN COMPARISON WITH ALBANIAN - Eda SHEHU (Езиков свят, 2025)
Noun gender, unlike number and case in Albanian, has been and continues to be studied within the grammatical system. However, it has increasingly become a subject of comparative research, particularly in relation to other languages. This study examines Russian and Albanian, focusing on both the commonalities and differences in the formation and functioning of nouns across the three genders in these languages. A key aspect of the analysis is the morphosyntactic perspective on gender, particularly the agreement of adjectives and pronouns with noun gender in both languages. For instance: (доклад) → мой интересный ←доклад → (работа) → моя интересная ← работа / (raport) - raporti → im interesant → (puna) – puna → ime interesante (my interesting ← report → my interesting work). The study also explores the relationship between grammatical gender and biological sex in gender categorization. Special attention is given to the neuter gender in Albanian, which lacks distinct grammatical markers, whereas in Russian, neuter nouns correspond to either feminine or masculine counterparts, e.g., të folurit (neuter) → а) речь (feminine), б) говор (masculine). Additionally, Russian nouns ending in a soft sign (мягкий знак -ь) can correspond to any of the three genders in Albanian. Understanding these similarities and differences in a comparative manner is crucial for the effective teaching of Russian as a foreign language to Albanian speakers. Identifying these distinctions enables Russian language instructors to address specific areas of interference, ultimately facilitating the learning process for Albanian students.